Non-Isolated Current-Fed Series Resonant Converter with Hybrid Control Algorithms for DC Microgrid - Byungki Kim; Hwa-Pyeong Park (Energies, 2023)
Module-level power electronics can optimize the power generation of photovoltaic panels, which requires a simple topology structure, high power conversion efficiency, and wide voltage gain, corresponding to irradiance variations. This paper proposes a non-isolated current-fed L-C series resonant converter and its control algorithms. The proposed converter can obtain a buck–boost voltage gain with the hybrid control algorithm utilizing the switching frequency modulation and asymmetric pulse width modulation. The proper power stage design can guarantee the soft-switching capability for the entire operating range. Also, the control strategy is designed to obtain a small rms current. The operational principle of proposed converter is analyzed in order to design the resonant tank and control strategy. The performance of designed converter can be verified with the experimental results with a 500 W prototype converter.